Intermetallic formation during soldering between lead-free solders and immersion silver surface finish / [compact disc] - Ch'ng, Emily Huey Ling, 1984- (Skudai : Universiti Teknologi Malaysia, 2007)
Project Paper (Sarjana Muda Kejuruteraan Mekanikal (Bahan)) - Universiti Teknologi Malaysia, 2007